1987
DOI: 10.1016/0044-8486(87)90060-3
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of gonadotropin release by neurohormones and gonadal steroids in the African catfish, Clarias gariepinus

Abstract: The secretion of gonadotropic hormone (GTH) from the pituitary of teleosts is considered to be regulated by neuropeptides and neuroamines of cerebral origin and steroid hormones from the gonads. This paper reviews our studies concerning the control of GTH release in the African catfish, Clarias gariepinus. It was demonstrated that luteinizing hormone releasing hormone (LHRH) stimulates GTH release and that the gonadotropin release-inhibiting activity of dopamine is restricted to the LHRH-induced GTH release. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 51 publications
2
23
1
Order By: Relevance
“…It could be argued that the rise in GTH, caused by the 17a-P injection, may be large enough to explain why this steroid induces ovulation, as well as oocyte maturation, in the African catfish. However, De Leeuw et al (1987) found that a LHRHa treatment usually would not cause ovulation in the African catfish, although the induced GTH levels are much higher than in the present experiment after 17~ P injection.…”
Section: Discussioncontrasting
confidence: 47%
“…It could be argued that the rise in GTH, caused by the 17a-P injection, may be large enough to explain why this steroid induces ovulation, as well as oocyte maturation, in the African catfish. However, De Leeuw et al (1987) found that a LHRHa treatment usually would not cause ovulation in the African catfish, although the induced GTH levels are much higher than in the present experiment after 17~ P injection.…”
Section: Discussioncontrasting
confidence: 47%
“…De Leeuw et al (1987), however, did observe an inhibitory effect of catecholestrogens on GTH relcase in catfish, indicating species-spccific differences in GTH regulation by steroids.…”
Section: The Involvement Of Gonadal Sterois In the Control Of Gonadotmentioning
confidence: 85%
“…An initial blood sample was 8 taken from all fish. Anaesthesia and surgery were carried out as described previously [13], except 9 that only one testis was removed. In sham-operated animals, the body wall was opened and closed 10 but both testes were left in place.…”
mentioning
confidence: 99%